Pengaruh Kompetensi, Independensi, Profesionalisme dan Akuntabilitas Auditor terhadap Kualitas Audit pada Kantor Akuntan Publik di Kota Medan - Rara Ivanka; Miftha Rizkina; Meigia Nidya Sari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study investigates how competence, independence, professionalism, and accountability impact audit quality in Medan City Public Accounting Firm (KAP). This study involved 39 auditors working for Medan City KAP. The sample was selected through purposive sampling method. The data collection method used a questionnaire that was distributed directly to respondents. Multiple linear regression analysis was used. The results of the study indicate that the competence variable partially has a negative and significant effect on audit quality. The independence variable also has a negative and significant effect on audit quality. Meanwhile, the professionalism variable has a positive and significant effect on audit quality. Likewise, the accountability variable, which also has a positive and significant effect on audit quality. Simultaneously, the competence, independence, professionalism, and accountability of auditors have a significant effect on audit quality.